Endoscopic augmentation of gastroesophageal junction using a full-thickness endoscopic suturing device - Han, Jimin (Endosc Int Open, 2018)
Background and study aims  This preliminary study was conducted to determine the feasibility and safety of endoscopic augmentation of the gastroesophageal junction (GEJ) using the Apollo OverStitch endoscopic suturing system in patients with gastroesophageal reflux disease (GERD) symptoms. Patients and methods  Endoscopic augmentation of GEJ was performed on 10 consecutive patients and the data were analyzed retrospectively. Using a double-channel gastroscope affixed to the endoscopic suturing platform, interrupted sutures were placed on the gastric side of the GEJ in 2 layers in order to create a narrowed and elongated GEJ. Results  Technical success was achieved in all patients, including those with a history of previous antireflux procedures (n = 7) and those with a hiatal hernia (n = 6). The median follow-up duration was 5 mo (range: 2 – 12). The median pre-procedure GERD-Health Related Quality of Life Questionnaire improved from 20 (range: 11 – 45) to a post-procedure score of 6 (range: 3 – 25) ( P  = 0.001). The median duration of GERD symptom improvement after the procedure was 1 mo (range: 0.5 – 4). Adverse events were limited to 1 patient who developed nausea and vomiting, which was self-limited. Conclusions  The use of a novel endoscopic suturing technique for the treatment of GERD is feasible and safe. The procedure resulted in short-term GERD symptom improvement. Further prospective studies using refined techniques are currently underway to improve durability and to prove efficacy.